Schule und Erziehung in der Deutschen Demokratischen Republik - Geissler, Gert (European Journal of Mental Health, 2011)
Schools and Education in the German Democratic Republic: Based on the publications of the last few years, the article provides an outline of the history of education in the former GDR, from the end of World War II up to the peaceful revolution in the autumn of 1989. The structural evolution of schools providing comprehensive education is presented with the typically dictatorial backdrop. Special attention is paid to the issues of access to education, the ‘equal rights to education’, and the assertion of the principle whereby state socialism constantly strove to prove its own legitimacy within the field of education. The paper identifies the political and ideological aspirations of the system in education, and the role teachers were to play in its implementation. Teacher training, primary school management and the basic characteristics of their activities are examined in further detail. The author describes the effects the internal social tensions, marking the entire history of the GDR, had on education, the tools the communist party employed in putting its ideas for education into practice, and how these ultimately failed.